Influence of Demographic Factors on Retirement Planning and Socio-Economic Status of Civil Servants in Uganda: Reflections from Pensioners from Busoga Sub-Region - Fabian, Mwosi; Charles, Edaku; Robina, Mirembe; Eton, Marus (Society & Sustainability, 2022)
This study provides a Ugandan perspective on the influence of demographic factors on retirement planning and the socio-economic status of civil servants. The study collected data from 236 pensioners using a questionnaire survey. The demographic factors included gender, marital status, age, income, and educational level. Using multiple regression, the study concludes that there is a low predictive influence of demographic factors on retirement planning and socio-economic status. Only educational level and monthly income have significant influences on retirement planning and the socioeconomic status of the retirees. This study offers a solid ground for increasing civil servants’ salaries in Uganda. Also, the government may consider identifying resources for the professional development needs of civil servants.